2020
DOI: 10.1080/23802359.2020.1765209
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome of the Smoothnose wedgefish Rhynchobatus laevis from the Western Indian Ocean

Abstract: We present the first mitogenome sequence of the Smoothnose Wedgefish, Rhynchobatus laevis obtained through field sequencing on the MinION handheld sequencer. The mitochondrial genome of R. laevis is 16,560 bp in length and consisted of 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes, and a non-coding control region (D-loop). GC content was at 40.1%. The control region was 867 bp in length. Whole mitochondrial genome sequence of R. laevis will enable improved understanding of distribution, abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Our sequencing and phylogenetic analyses in the current study corroborates the taxonomic classification of five species (R. punctifer, T. sinuspersici, C. sorrah, M. mobular, and the M. tarapacana) in the sample set. Taxonomic identifications for Carcharhinus falciformis (Johri et al, 2019), Rhynchobatus laevis (Johri et al, 2020c), and Glaucostegus granulatus (Johri et al, 2020b) were confirmed previously by us. It should be noted that the low posterior probabilities or bootstrap support values in case of T. sinuspersici, Bayesian and maximum likelihood analyses are due to the lack of enough genetic data available for this clade of species in public databases.…”
Section: Discussionsupporting
confidence: 77%
“…Our sequencing and phylogenetic analyses in the current study corroborates the taxonomic classification of five species (R. punctifer, T. sinuspersici, C. sorrah, M. mobular, and the M. tarapacana) in the sample set. Taxonomic identifications for Carcharhinus falciformis (Johri et al, 2019), Rhynchobatus laevis (Johri et al, 2020c), and Glaucostegus granulatus (Johri et al, 2020b) were confirmed previously by us. It should be noted that the low posterior probabilities or bootstrap support values in case of T. sinuspersici, Bayesian and maximum likelihood analyses are due to the lack of enough genetic data available for this clade of species in public databases.…”
Section: Discussionsupporting
confidence: 77%
“…Whole mitochondrial genome sequence of T. obesus from the Chagos archipelago presented here fills existing gaps in genetic information from the BIOT MPA. In addition, the data presented here alongwith our previously published work in the Chagos archipelago (Ferretti et al 2018;Dunn et al 2020;Tickler et al 2019;Johri et al 2020) will enable species specific assessments of top predators in the BIOT MPA and provide metrics to assess the effectiveness of MPA management. Last, methods described here lay the framework for future molecular studies in study sites with limited laboratory infrastructure.…”
mentioning
confidence: 85%
“…The specimen was stored at the Hopkins Marine Station, Stanford University in 70% ethanol (Sample Accession # 020002232503). DNA was extracted from the muscle biopsy of an individual mature male and the mitochondrial genome was sequenced on the MinION sequencer using published methods (Johri et al 2019;Dunn et al 2020;Johri et al 2020;Johri et al 2020;Johri et al 2020). 302,000 Fast5 files obtained from sequencing were converted to FASTQ files, and processed as described in (Johri et al 2019), resulting in a contig of 165 reads.…”
mentioning
confidence: 99%
See 2 more Smart Citations